Weighted pseudorandom hybrid BIST. - Jas, A.
This paper presents a new test data-compression scheme that is a hybrid approach between external testing and built-in self-test (BIST). The proposed approach is based on weighted pseudorandom testing and uses a novel approach for compressing and storing the weight sets. Three levels of compression are used to greatly reduce test costs. Experimental results show that the proposed scheme reduces tester storage requirements and tester bandwidth requirements by orders of magnitude compared to conventional external testing, but requires much less area overhead than a full BIST implementation providing the same fault coverage. No test points or any modifications are made to the function logic. The paper describes the proposed hybrid BIST architecture as well as two different ways of storing the weight sets, which are an integral part of this scheme.
Keywords: Built in self test; External testing; Fault coverage; Function logic; Hybrid BIST architecture; Hybrid method; Test cost reduction; Test data compression; Tester bandwidth requirements; Tester storage requirements; Weight set compression; Weight set storage; Weighted pseudorandom testing